A 457 nW Near-Threshold Cognitive Multi-Functional ECG Processor for Long-Term Cardiac Monitoring - Liu, Xin (2016)
A low-power multi-functional electrocardiogram (ECG) signal processor is presented in this paper. To enable long-term monitoring, several architecture-level power saving techniques are proposed, including global cognitive clocking, pseudo-downsampling wavelet transform, adaptive storing, and denoising-based run-length compression. An ultra-low-voltage ADC is designed for low-power signal digitization with adaptive clocking. Through these architecture-level techniques, the total power consumption can be significantly reduced by 63% as compared to the conventional design. Several circuit-level design techniques are also developed, including ultra-low-voltage operation and near-threshold level shifting, to further reduce the power consumption by 33%. In addition, a low-complexity cardiac analysis scheme is proposed to realize comprehensive on-chip cardiac analysis. Implemented in 0.18 μm CMOS process, the proposed cognitive ECG processor consumes only 457 nW at 0.5 V for real-time ECG recording and diagnosis.